Handbook of Supernovae 2017
DOI: 10.1007/978-3-319-20794-0_42-1
|View full text |Cite
|
Sign up to set email alerts
|

Type Iax Supernovae

Saurabh W. Jha

Abstract: Type Iax supernovae (SN Iax), also called SN 2002cx-like supernovae, are the largest class of "peculiar" white dwarf (thermonuclear) supernovae, with over fifty members known. SN Iax have lower ejecta velocity and lower luminosities, and these parameters span a much wider range, than normal type Ia supernovae (SN Ia). SN Iax are spectroscopically similar to some SN Ia near maximum light, but are unique among all supernovae in their late-time spectra, which never become fully "nebular". SN Iax overwhelmingly oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…Ia-TDEs are expected to appear spectroscopically similar to SNe Ia, but with lower luminosity. This is reminiscent of SNe Iax, a class of SN characterized by low photospheric velocities of ∼ 2000 − 8000 km s −1 during peak, hot photospheres, and low peak luminosities between −14.2 M V −18.9 (Foley et al 2013;Jha 2017;Lee & Shen 2022). One leading model to explain SNe Iax is a pure-deflagration explosion of a CO-WD, where the explosion is triggered by accretion of helium onto the WD, which does not necessarily fully disrupt the star (Jha 2017).…”
Section: Comparison To Sne Iamentioning
confidence: 97%
See 1 more Smart Citation
“…Ia-TDEs are expected to appear spectroscopically similar to SNe Ia, but with lower luminosity. This is reminiscent of SNe Iax, a class of SN characterized by low photospheric velocities of ∼ 2000 − 8000 km s −1 during peak, hot photospheres, and low peak luminosities between −14.2 M V −18.9 (Foley et al 2013;Jha 2017;Lee & Shen 2022). One leading model to explain SNe Iax is a pure-deflagration explosion of a CO-WD, where the explosion is triggered by accretion of helium onto the WD, which does not necessarily fully disrupt the star (Jha 2017).…”
Section: Comparison To Sne Iamentioning
confidence: 97%
“…This is reminiscent of SNe Iax, a class of SN characterized by low photospheric velocities of ∼ 2000 − 8000 km s −1 during peak, hot photospheres, and low peak luminosities between −14.2 M V −18.9 (Foley et al 2013;Jha 2017;Lee & Shen 2022). One leading model to explain SNe Iax is a pure-deflagration explosion of a CO-WD, where the explosion is triggered by accretion of helium onto the WD, which does not necessarily fully disrupt the star (Jha 2017). It is likely that if Ia-TDEs are detected, they might appear classified as SNe Iax, as is the case for the nuclear Ia-TDE candidates SN 2021jun, and SN 2020lrt.…”
Section: Comparison To Sne Iamentioning
confidence: 97%
“…It has been suggested that SNe Iax could arise from weak deflagration explosions of Chandrasekhar-mass WDs in which the stars are not fully disrupted. Such events would leave behind a bound WD remnant that has been shock heated significantly (Jordan et al 2012a;Foley et al 2013;Kromer et al 2013a;Fink et al 2014;Jha 2017). If binary systems are destroyed by the SN explosion in this model, such partly burnt WD remnants would be ejected with a high velocity and a peculiar atmosphere due to enrichment with heavy elements from the SN explosion, causing some unusual observational features (Shen et al 2017;Zhang et al 2019).…”
Section: Searches For Surviving Wd Remnantsmentioning
confidence: 97%
“…These SNe Ia are usually referred to as "normal SNe Ia," and they have long been used as standardizable candles for measuring cosmological distances (Leibundgut 2001(Leibundgut , 2008Goobar & Leibundgut 2011). However, an increasing number of SNe Ia have been observed that do not follow the Phillips relation (see Figure 1), and they are diverse in their observational characteristics, such as light curve shape, peak luminosity and spectral features (Benetti et al 2005;Blondin et al 2012;Jha 2017). For these reasons, SNe Ia have been classified into different subclasses diverging from normal events, which include 1991T-likes (Filippenko et al 1992a;Phillips et al 1992), 1991bg-likes (Filippenko et al 1992b;Leibundgut et al 1993Li et al 2003;Foley et al 2013), 2002es-likes (Ganeshalingam et al 2012), calcium (Ca)-rich objects (i.e., SN 2005E-like; Perets et al 2010;Kasliwal et al 2012), super-Chandrasekhar objects (i.e., SN 2003fg-likes; Howell et al 2006;Hicken et al 2007), SNe Ia-CSM (Hamuy et al 2003) and fast decliners (Taubenberger 2017).…”
Section: Diversity Of Sne Iamentioning
confidence: 99%
See 1 more Smart Citation